Association among Vitamin D Deficiency with some Inflammatory Marker in Iraqi Patients with Autoimmune Thyroiditis - Noor Alhuda Kh. Ibrahim1, Zaid Nsaif Abbas2, Wasnaa J. mohammad1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Hashimoto thyroiditis (HT) is a common chronic autoimmune disease of the thyroid gland, characterized by painless goiter and elevated thyroid antibodies. Hypovitaminosis D (vitamin D insufficiency and deficiency) is common among patients with HT.Method: : the study include (60) subjects compared with 30 apparently healthy control group were visiting nursing home hospital in Baghdad medical city, Levels of serum thyroid-stimulating hormone (TSH), free-triiodothyronine (FT3), free thyroxine (FT4), TgAbs, and TPOAbs were determined with automated immuno chemiluminescent assay (ICMA) kits (Abbott Laboratories, IL, USA). Levels of serum 25-hydroxyvitamin D 25(OH) D) were determined using a competitive protein-binding assay (Roche Diagnostics, Mannheim, Germany). The inter-assay variation coefficient for 25(OH)D measurement was 8.5%.Results: the level of the study parameters in autoimmune thyroiditis which show significant correlation in age ,BMI, vitamin D, anti TPO antibody,IL-17, TNF-? and thyroid function (p<0.05) (p<0.01) test but calcium shoe non significant correlation between patients and control group.Conclusion: The present work shows a significant association between circulating 25(OH)D and HT, also IL-17.